2022
DOI: 10.14202/vetworld.2022.2039-2045
|View full text |Cite
|
Sign up to set email alerts
|

Broad lytic spectrum of novel Salmonella phages on ciprofloxacin-resistant Salmonella contaminated in the broiler production chain

Abstract: Background and Aim: Ciprofloxacin (CIP) is recommended for salmonellosis treatment as the drug of choice; however, overuse of this drug can cause drug resistance issues and failure to treat diseases. Phage therapy is an alternative approach for combatting CIP-resistant infection. This study aimed to estimate the prevalence of CIP-resistant Salmonella isolated from the broiler production chain and evaluated the lytic ability of novel Salmonella phages isolated from water samples. Materials and Methods: Samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Salmonella phage applications are already used in many countries in the food sector to avoid food contamination. Phage therapy in animal production is also reaching the stage of large-scale industrial trials [ 24 , 25 , 26 , 27 ]. However, these applications can be controversial, as phages drive bacterial evolution in Salmonella in the fastest and most effective way [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella phage applications are already used in many countries in the food sector to avoid food contamination. Phage therapy in animal production is also reaching the stage of large-scale industrial trials [ 24 , 25 , 26 , 27 ]. However, these applications can be controversial, as phages drive bacterial evolution in Salmonella in the fastest and most effective way [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diverse serovars of Salmonella were recovered in the broiler production chain in that study, while the isolates presenting ciprofloxacin-resistant Salmonella were as high as 29.4%. Overall, Salmonella phages showed high lysis ability against these ciprofloxacin-resistant Salmonella isolates, suggesting the potential application of phage-based treatments or biocontrol in the broiler production chain ( Pelyuntha et al, 2022 ). Grabowski et al (2022) indicated for the first time that cocktail of phages targeting Salmonella is not only effective but also can be used in veterinary practices without disturbing immune homeostasis, expressed as cytokine imbalance, disturbed percentage of key immune cell subpopulations, and stress axis hyperactivity.…”
Section: Phage Therapy Of Bacterial Infections and Zoonotic Agents In...mentioning
confidence: 99%
“…The results of this study indicated that isolated phages could lyse (ranging from 33.3% to 93.3%) ciprofloxacin‐resistant bacteria. These data suggest that phages have a promising potential in combating ciprofloxacin‐resistant Salmonella isolates in the broiler production chain and preventing their spread through the food supply chain 2 . In another study, a Salmonella Typhi isolates with decreased susceptibility to ciprofloxacin and producing CTX‐M‐15 extended spectrum‐lactamase (ESBL) was isolated in the Democratic Republic of the Congo.…”
Section: The Use Of Phages For Ciprofloxacin‐resistant Bacteriamentioning
confidence: 99%
“…1 Ciprofloxacin resistance in different bacteria has been increasingly reported worldwide because of mutations in DNA gyrase genes (gyrA), efflux pumps, or plasmidmediated-quinolone resistance in bacterial plasmids or chromosomes. 2 In this regard, applying a combination of different substances such as nanoparticles, natural compounds, and bacteriophages with ciprofloxacin to enhance the efficacy of this antibiotic against multi-drug resistant (MDR) bacteria has received much attention. 3 Bacteriophages (phages) are viruses that could lyse bacteria while are not harmful to animal and human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation